Is hemolysis a novel therapeutic target in COVID-19? - Ousaka, Daiki; Nishibori, Masahiro (Frontiers in Immunology, 2022)
As of February 2022, despite the repeated administration of booster vaccines, COVID-19 continues to cause surges of infection around the world due to the occurrence of mutant viruses. Nonetheless, in the past two years, many details of the pathways of infection and pathological mechanisms have been uncovered, and various drugs have been discovered for the prevention and treatment of severe COVID-19. However, both for the current and for future pandemics, we must continue to pursue the development of new therapeutic strategies that inhibit acute respiratory distress syndrome (ARDS) and associated thrombosis. Previous studies have revealed several comorbid conditions associated with severe COVID-19, such as impaired immune response, systemic inflammatory response syndrome (SIRS), and thromboembolism, most of which appear to be related to hemolysis in either the intravascular or interstitial spaces . In this focused review, we discuss the relationship between COVID-19 severity and hemolysis, which includes the underlying mechanisms, potential as a therapeutic target, and issues for drug candidates.